Basal cell carcinoma of the ala of nose: a case report - Prathyusha, G; Singh, T. Dinesh; Kiran, G. Abhinav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Basal cell carcinoma (BCC) of nose is common with potential of local recurrence and high risk features. We are reporting a case of BCC on the right ala of nose in an elderly female patient hailing from rural background, who came to our OPD for cosmetic outcome. She was treated with wide local excision with nasolabial flap reconstruction. The tissue when sent for HPE came up with BCC with margin involvement. Hence she was sent to chemoradiotherapy after 3 weeks of surgery, after complete wound healing.